Intratumor Heterogeneity as a Prognostic Factor in Solid Tumors: A Systematic Review and Meta-Analysis - Yu, Tao; Gao, Xin; Zheng, Zicheng; Zhao, Xinyu; Zhang, Shiyao; Li, Chunqiang; Liu, Gang (Frontiers in Oncology, 2021)
Background: The landscape of intratumor heterogeneity(ITH) was present from the tumor evolution. ITH is a promising clinical indicator but the association between ITH and prognosis remains controversial. Therefore, a meta-analysis was performed to explore whether ITH can serve as an independent prognostic indicator in solid tumors. Methods:All including studies from PubMed, Embase, Cochrane, Web of Science databases up to October 10, 2020. Studies based on ITH with available prognostic information were included. Three researchers independently completed study selection and data extraction following PRISMA guidelines. The random-effect model was used for synthesis. Hazard ratio (HR) and 95% confidence intervals (CI) with the endpoint defined by overall survival (OS), disease-specific survival (DFS), and progression-free survival (PFS). Results: A total of 9,804 solid tumor patients from 21 studies were included. Analysis of specific cancers in the TCGA database showed similar results based on different ITH assessment methods, which provided the logical support for data consolidation. Available evidence revealed a negative relationship between ITH and prognosis for specific cancer(such as lung cancer). However, the OS results from 14 tumor types showed that high ITH associated with shorter survival time (HR1.65 [95% CI, 1.42–1.91]). PFS and DFS analyses showed similar results(HR1.89 [95%CI, 1.41–2.54] and HR1.87 [95%CI, 1.15–3.04]) in general. The status of tumor metastasis and sampling models were not the confounding factors. Conclusions: High ITH is associated with worse prognosis in many solid tumors in general although this association was absent for some cancers. ITH is expected to be a promising clinical prognostic factor for the improvement of assessment, treatment, and surveillance strategy.